REVITALISASI PESANTREN DI ERA DIGITAL DALAM MEWUJUDKAN LINGKUNGAN BERSIH DAN TEKNOLOGI TERAPAN UNTUK INOVASI YANG BERDAMPAK DAN BERKELANJUTAN DI PONPES MIFTAHUL HUDA MALANG - Firdausi, Rofiqoh; Huda, Moh. Khoridatul; Iza, Belgis Ainatul; Laili, Nurul (FIP UNIRA MALANG, 2025)
The revitalization of Islamic boarding schools in the digital era is a strategic initiative to enhance environmental quality and foster the application of applied technology. This community engagement program aims to establish a clean, healthy, and technologically adaptive environment at Miftahul Huda Islamic Boarding School, Malang. Using a participatory approach—consisting of awareness campaigns, training, and continuous mentoring—the program focused on environmental cleanliness, organic waste composting, and the implementation of a digital information system for student administration. The outcomes revealed significant improvements in students’ environmental awareness, successful organic compost production, and the adoption of digital systems to streamline school management. Beyond improving environmental quality, the program equipped students with relevant digital literacy. This sustainable model offers potential replication in other Islamic boarding schools to support impactful innovation.